Theoretical study of the formation of C18H and C18H2 molecules by low energy irradiation with atomic and molecular hydrogen - Domínguez-Gutiérrez, Javier F.; Martínez-Flores, César; Krstic, P. S.; Cabrera-Trujillo, Remigio; Toussaint, Udo von (Radiation physics and chemistry, 2021)
We study the formation of C18H and C18H2 by irradiating a cyclo [18]carbon molecule with atomic and molecular hydrogen at impact energy, E, in the range of 0.5-25 eV. We utilize the density-functional tight-binding method to perform molecular dynamics simulations to emulate the interaction of a carbon ring when colliding with atomic or molecular hydrogen. From our results, the formation of the C18H molecules is likely to occur upon irradiating by H atoms at E<10 eV and by H2 molecules at 2<E<15 eV center of mass energy. Formation of C18H2 molecules is only observed at around E=2 eV. Our results show that the absorption of hydrogen is more prone in atomic than in molecular hydrogen atmosphere. Thus, we find that the probability of physio-absorption reaches up to 80% for atomic projectiles with E<5 eV but only up to 10% for the molecular ones. Our analysis shows that the deformation of the carbon ring due to the hydrogen bonding produces transition from sp to sp2 hybridization. The angle between the carbon atoms at the locations near to the H bond in the resulting ring is not 120° but instead 110° degrees. No molecular fragmentation of the C18 ring is observed.